THE INFLUENCE OF PRODUCT QUALITY, LIFESTYLE, BRAND IMAGE, AND PRICE ON PURCHASING DECISIONS ON IPHONE SMARTPHONE PRODUCTS IN BEKASI CITY (CASE STUDY OF USERS OF USED IPHONE SMARTPHONES IN BEKASI CITY) - Christian Gideon Mandagi; Muhammad Richo Rianto; Choiroel Woestho (Draf Solusi Indonesia, 2024)
This research is research used to measure the influence of product quality, lifestyle, brand image and price on purchasing decisions for used iPhone smartphone products in Bekasi City. The technique used was accidental sampling technique with the number of samples used in this research being 113 respondents. Hypothesis testing using SmartPLS 3.0. The results of this research provide an explanation that lifestyle variables do not significantly influence the decision to purchase used iPhone smartphone products in Bekasi City. However, the variables product quality, brand image and price have a significant influence on purchasing decisions for used iPhone smartphone products in Bekasi City. This research has the limitation of the research object being that it was only conducted on used iPhone smartphone users in Bekasi City. This can be a suggestion for future researchers. The novelty in this research combines the variables of product quality, lifestyle, brand image and price on purchasing decisions for used iPhone smartphone products in Bekasi City.